Web-based SIA Pranata Sejahtera Using Laravel - Anggoro Bagus Dewaji; Albertus Dwiyoga Widiantoro; Agnes Advensia Chrismastuti (Soegijapranata Catholic University, 2022)
Pranata Sejahtera Cooperative is a savings and loan institution provided by Soegijapranata Catholic University for its employees. Based on interviews conducted with the treasurer and officers of the cooperative, the cooperative faces several problems. Some records exist using semi-manual methods, such as recording transactions from deposits, loans, and registered members. The next problem, cooperatives have experienced losses due to fraud in management financialBased on the problems experienced by the Pranata Sejahtera Soegijapranata cooperative, the researcher provides a solution for making a web-based accounting information system with the Laravel framework.